Metabolism of L-glyceraldehyde 3-phosphate in Escherichia coli. - Kalyananda, M K (1987)
When either 3H-labeled L-glyceraldehyde or 3H-labeled L-glyceraldehyde 3-phosphate (GAP) was added to cultures of Escherichia coli, the phosphoglycerides were labeled. More than 81% of the label appeared in the backbone of the phosphoglycerides. Chromatographic analyses of the labeled phosphoglycerides revealed that the label was normally distributed into phosphatidylethanolamine, phosphatidylglycerol, and cardiolipin. These results suggest that L-glyceraldehyde is phosphorylated and the resultant L-GAP is converted into sn-glycerol 3-phosphate (G3P) before being incorporated into the bacterial phosphoglycerides. Cell-free bacterial extracts catalyzed an NADPH-dependent reduction of L-GAP to sn-G3P. The partially purified enzyme was specific for L-GAP and recognized neither D-GAP nor dihydroxyacetone phosphate as a substrate. NADH could not replace NADPH as a coenzyme. The L-GAP:NADPH oxidoreductase had an apparent Km of 28 and 35 microM for L-GAP and NADPH, respectively. The enzyme was insensitive to sulfhydryl reagents and had a pH optimum of approximately 6.6. The phosphonic acid analog of GAP, 3-hydroxy-4-oxobutyl-1-phosphonate, was a substrate for the reductase, with an apparent Km of 280 microM.